Effect of natural oils on the thermal stability and degradation kinetics of recycled polypropylene wood flour composites. Issue 10 (13th January 2014) - Poletto, Matheus; Zattera, Ademir J.; Santana, Ruth M.C.
<x xml:space="preserve">Abstract</x> Recycled polypropylene was reinforced with wood fibers that were non‐treated and treated with different natural oils (hexanoic, octanoic, decanoic and dodecanoic acids). The thermal properties, morphology, kinetics and thermodynamic parameters were investigated. The use of natural oils as coupling agents clearly improved the interfacial adhesion with the matrix and increased the thermal stability of the composites. Octanoic acid improved the thermal stability of the composite the most compared with the other evaluated natural oils. The improvement caused by this natural oil is similar to that promoted by the addition of PPgMA. The thermal stability of the composite was affected by the boiling temperature and the chain length of the acid used. POLYM. COMPOS., 35:1935–1942, 2014. © 2014 Society of Plastics Engineers